The Relationship of Disease Perception and Duration of Suffering to Self-Care Management in Patients with Diabetes Mellitus in Rimbo Recap Village, South Curup District, Rejang Lebong Bengkulu 2025 - Rustam Aji Rochmat; M Ramadhani Firmansyah; Rahayu Tri Nuritasari; Yeni Trisna Purba; Esa Zahirah (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Self-care management is a crucial element in Diabetes Mellitus (DM) control, but is influenced by internal factors such as disease perception and duration of illness. This study aims to analyze the relationship between disease perception and duration of suffering with self-care management in patients with DM in Rimbo Recap Village, South Curup District, Rejang Lebong Regency, Bengkulu Province. Methods: This research design is quantitative cross- sectional with a sample of 60 DM patients selected by purposive sampling from the patient list of the Watas Marga Health Center. Results: There is a significant relationship between disease perception (p = 0.002) and duration of suffering (p = 0.000) with self-care management in patients with DM. Conclusion: Continuous educational interventions and psychosocial strategies are recommended to improve positive perceptions and maintain long-term self-care behaviors.